ENGLISH FOR ISLAMIC STUDIES (EIS) - Ilzamudin Ma'mur (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2005)
English jor Islamic Studies (from now on, EIS) is a kind of English for Academic Purposes that should be taken by all the students, mostly with multilingual backgrounds, at the Islamic higher educational institutions either run by the government or by private education faundations in Indonesia. One of the main of objective of EIS is to help the students improve their reading skill so as to be able to handle a variety of English written texts on